Pengembangan Media Pembelajaran dengan Pendekatan Saintifik pada Materi Teorema Pythagoras - Fauziah, Nita Fatma; Hadiyanto, Fahrur Rozi (FKIP Universitas Mataram, 2021)
The Pythagorean Theorem is an important material to study because the application of this material is used to study other material in mathematics as well as in other subjects. The success of students in learning the Pythagorean theorem material can be influenced by several factors, one of which is the way the teacher teaches the material. A valid and practical learning media is one way of teaching the Pythagorean theorem so that it is better understood by students. The purpose of this research is to produce a valid and practical Pythagorean theorem learning media. The learning media (students work sheet) development model refers to the Plomp development model which consists of: (1) the initial investigation stage, (2) the design stage, (3) the realization stage, and (4) the test, evaluation, and revision stages. Based on the analysis of development data, it is found that the learning media developed are valid and practical.ÃƒÂ‚Ã‚Â AbstrakÃƒÂ‚Ã‚Â Theorema Pytagoras adalah materi yang penting untuk dipelajari karena aplikasi maetri ini digunakan untuk mempelajari materi lain dalam matematika dan pelajaran lain. Keberhasilan dalam memepelajari materi teorema Pythagoras salah satunya dapat dipengaruhi oleh cara guru dalam membelajarkan materi ini. Media pembelajaran yang valid dan praktis adalah salah satu cara membelajarkan materi teorema Pythagoras agar lebih dipahami oleh siswa. Tujuan ÃƒÂ‚Ã‚Â dalam penelitian ini adalah untuk menghasilkan media pembelajaran teorema Pythagoras yang valid, dan praktis. Model pengembangan media pembelajaran mengacu pada model pengembangan Plomp yang terdiri atas: (1) tahap investigasi awal, (2) tahap desain, (3) tahap realisasi, dan (4) tahap tes, evaluasi, dan revisi. Berdasarkan analisis data pengembangan diperoleh hasil bahwa media pembelajaran yang dikembangkan dinyatakan valid, dan praktis.ÃƒÂ‚Ã‚Â